2014
DOI: 10.1111/myc.12200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of systemic corticotherapy on the triggering of pityriasis versicolor

Abstract: Pityriasis versicolor is a frequent mycosis and the use of systemic corticotherapy is one of its predisposing factors. This is an observational, cross-sectional, analytical and comparative study, conducted from January 2012 to January 2013 in the following outpatient clinics: Dermatology Service, Cassiano Antonio Moraes Hospital (HUCAM), Vitória, ES, Brazil; Nephrology Service, HUCAM; and Leprosy Department, Maruípe Health Unit, Vitória, ES, Brazil. Patients, undergoing long-term systemic corticotherapy (or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…He et al state that up to 21% of patients report a positive family history implying a possible genetic predisposition [9]. Alternative risk factors for TV include heat, humidity, excessive perspiration, Cushing syndrome, long-term immunosuppressive corticosteroid use, pregnancy, diabetes mellitus, and poor nutrition [10][11][12]. Under the conditions associated with these risk factors, the yeast form of Malassezia changes to the mycelial form leading to clinical disease.…”
Section: Introductionmentioning
confidence: 99%
“…He et al state that up to 21% of patients report a positive family history implying a possible genetic predisposition [9]. Alternative risk factors for TV include heat, humidity, excessive perspiration, Cushing syndrome, long-term immunosuppressive corticosteroid use, pregnancy, diabetes mellitus, and poor nutrition [10][11][12]. Under the conditions associated with these risk factors, the yeast form of Malassezia changes to the mycelial form leading to clinical disease.…”
Section: Introductionmentioning
confidence: 99%
“…Predisposing factors for the conversion include a hot and humid environment, hyperhidrosis, application of oily lotion or cream to the skin, wearing of masks, excessive lipid-containing sebaceous secretions, malnutrition, poor general health, use of oral contraceptives, pregnancy, diabetes mellitus, use of topical or systemic corticosteroids, Cushing disease, Helicobacter pylori infection, immunodeficiency and genetic predisposition. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] A recent study showed oxidative stress has no role in the pathogenesis of tinea versicolor. 29…”
mentioning
confidence: 99%